Quantitative analysis of customer’s emotional experience in restaurants on the Opatija Riviera - Marković, Suzana; Raspor Janković, Sanja; Gjurašić, Matina (Oeconomica Jadertina, 2021)
Experience economy is not about people buying products and services. Instead, they buy experiences that lead to strong emotions and reactions. Although service quality and customer satisfaction concepts have been under study for many years, they are still in the focus of scientific and practical research. However, there is a small number of studies that aim to measure and research customers’ emotional experience in restaurants. The main purpose of the present study is to analyse previous researches regarding these concepts, and to develop an instrument DINEXPE for measuring customers’ emotional experience in restaurants. For this purpose, measurement instrument with 35 variables was created and data was analysed using statistical methods. The sample consists of 195 restaurant customers who visited Lovran gastronomic festival (Opatija Riviera, Croatia) in April 2018. The research findings can be useful to restaurant managers to better understand their guests in designing service quality that meets guests’ expectations.
Keywords: service quality; satisfaction; loyalty; emotions; Opatija Riviera restaurants; quantitative analysis